2019
DOI: 10.1016/j.jamda.2019.03.033
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Incidence, and Correlates of Fecal Incontinence Among Older People Residing in Care Homes: A Systematic Review

Abstract: Objective: Older people resident in care homes often rely on staff for support relating to their activities of daily living, including intimate care such as continence care. Managing fecal incontinence can be challenging for both residents and care staff. We conducted this review to describe the prevalence, incidence, and correlates of fecal incontinence among care home residents. Design: Systematic literature review. Setting and participants: Older care home residents (both nursing and residential care) aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 49 publications
3
39
2
Order By: Relevance
“…Walking is directly associated with mobility, a serious challenge in nursing homes. 32 Immobility is associated with multiple adverse health and quality of life outcomes (eg, fecal incontinence, pressure ulcers, skin tears). [32][33][34] Both talking and walking with residents are associated with care quality and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Walking is directly associated with mobility, a serious challenge in nursing homes. 32 Immobility is associated with multiple adverse health and quality of life outcomes (eg, fecal incontinence, pressure ulcers, skin tears). [32][33][34] Both talking and walking with residents are associated with care quality and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…It concerns both men and women. It more often affects the elderly, especially patients staying in nursing homes, and it may be associated with limited mobility and care possibilities [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due in part to the profound cognitive deficits and functional impairments that can render these individuals less active and less communicative about their health, thereby increasing their risk of infections 50 . In nursing home residents, urinary tract infections are the most commonly diagnosed infections, which may also be due to reduced hygiene associated with urinary and fecal incontinence in this population 51–53 . Studies have also shown that incontinence may lead to an increased risk of urinary tract infections in residents with agitation who may be more likely to refuse care from staff 54 .…”
Section: Discussionmentioning
confidence: 99%